Spin-Echo Micro-MRI of Trabecular Bone Using Improved 3D FLASE - Magland, JF (2009)
Fast Large-Angle Spin Echo (FLASE) is a common pulse sequence designed for quantitative imaging of trabecular bone micro-architecture. However, imperfections in the nonselective phase-reversal pulse render it prone to stimulated echo artifacts. The problem is further exacerbated at isotropic resolution. Here, a substantially improved RF-spoiled FLASE sequence (sp-FLASE) is described and its performance illustrated with data at 1.5 and 3T. Additional enhancements include navigator echoes for translational motion sensing applied in a slice parallel to the imaging slab. Whereas recent work suggests the use of fully balanced FLASE (b-FLASE) to be advantageous from a SNR point of view, evidence is provided here that the greater robustness of sp-FLASE may outweigh the benefits of minor SNR gain of b-FLASE for the target application of trabecular bone imaging in the distal extremities, sites of exclusively fatty marrow. Results are supported by a theoretical Bloch equation analysis and the pulse sequence dependence of the effective T2 of triglyceride protons. Lastly, sp-FLASE images are shown to provide detailed and reproducible visual depiction of trabecular networks in three dimensions at both anisotropic (137×137×410 µm(3)) and isotropic (160×160×160 µm(3)) resolutions in the human distal tibia in vivo.